The Effects of Red Onion Peel Liquid Organic Fertilizer and NPK Fertilizer on Chlorophyll Content and Vegetative Growth of Kangkung Darat (Iphomoea reptans Poir) - Jannah, Raudatul; Raksun, Ahmad; Wirajagad, Gde Cahyadi (Jurnal Biologi Tropis, 2026)
This study aimed to determine the effect of red onion peel Liquid Organic Fertilizer, NPK fertilizer, and their interaction on the chlorophyll content and vegetative growth of Kangkung Darat. The research used a completely randomized design factorial with two factors: Liquid Organic Fertilizer dosage (0, 10, 20, 30 ml) and NPK dosage (0, 0.5, 1, 1.5 g). Four nitrogen rates (25%, 50%, 75%, and 100% of the recommended dose) and two phosphorus rates (50% and 100% of the recommended dose), each replicated three times, were used in the factorial Randomized Complete Block Design experiment, which was carried out in Rembige Village, Mataram City, between February and April of 2026. Analysis of variance and the Honestly Significant Difference test at the 5% significance level were used to evaluate the data. At 42 and 49 days following planting, nitrogen had a substantial impact on both the number of bulbs per clump and plant height. While the interplay between nitrogen and phosphorus had a substantial impact on leaf chlorophyll content, phosphorus had a considerable impact on bulb number, bulb diameter, and fresh bulb weight. This study concludes that the application of red onion peel Liquid Organic Fertilizer can complement or optimize the efficiency of NPK fertilizer, reducing environmental reliance on chemical inputs.